Influence of Preoperative Foveal Layers’ Thickness on Visual Function and Macular Morphology by Phacovitrectomy for Epiretinal Membrane - R Zhmurin; L Grajewski; L Krause (Journal of Ophthalmology)
Background. The aim of this retrospective study with short, differently dispersed follow-up is to record the relationships between the pathologies of the individual foveal layers, measured by spectral domain optical coherence tomography (SD-OCT), and to investigate their influence on pre- and postoperative best-corrected decimal far visual acuity (BCVA) by phacovitrectomy for epiretinal membrane (ERM) in comorbidity with cataract. Patients and Methods. 208 eyes of 173 patients with symptomatic idiopathic ERM and moderate cataract were included. Results. In all OCT morphological stages of ERM, as well as in their combination with macular lamellar hole (MLH) and vitreomacular traction (VMT), a significant difference in the thickness of the individual fovea layers was found. In addition, the entire fovea thickening led to the proportional thickening of the individual fovea layers (p<0.001). The larger the central foveolar (CFT, R2 = −0.238, p=0.002), maximum foveal (MFT, R2 = −0.267, p=0.001), and ONL thickness (R2 = −0.16, p=0.044) were preoperatively, the worse the initial visual acuity was at all OCT stages of ERM. This was even more significant in the presence of a tractive component in the case of MLH or VMT (p<0.001). In ERM without a traction component, only ONL thickening led to significant postoperative visual acuity reduction (R2 = −0.163, p=0.047). The foveolar retinal thickening (CFT and MFT) of the pure ERM is directly associated with distortion of the retinal layers (R2 = 0.292, p<0.001 and R2 = 0.287, p<0.001) as well as with separation of the ERM (R2 = 0.168, p=0.034 and R2 = 0.187, p=0.018). When ERM was combined with tractive component, CFT, ONL, and INL thickness correlated (positively) with the integrity of ellipsoid zone (R2 = 0.342, p<0.05) and external limiting membrane (R2 = 0.548, p<0.001). Conclusions. ONL thickening in ERM without a tractive component serves as a limited prognostic factor of postoperative visual acuity decrease. The preoperative BCVA in the groups of ERM with traction component showed significant correlation with CFT as well as with the thickness of individual foveal layers. VMT in ERM correlates with the disintegration of the ellipsoid zone.